2017
DOI: 10.1123/ijatt.2015-0103
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Nordic Hamstring Exercises in Reducing Hamstring Injuries in Competitive Soccer Players: A Critically Appraised Topic

Abstract: Clinical Question:Are Nordic hamstring exercises more effective than standardized training in reducing hamstring strain injury rates in competitive soccer players over the course of at least one season?Clinical Bottom Line:The evidence supports the use of Nordic hamstring exercises to reduce hamstring injury incidence rates over a competitive soccer season. Therefore, progressive Nordic hamstring exercises should be included within some aspect of a practice to prevent the occurrence of hamstring injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Fifteen RCT studies were included, all of which had a training frequency of 1-5 sessions per week, and a subgroup analysis showed that a hamstring eccentric training regimen lasting 21-30 weeks was the most effective in preventing lower extremity injuries, resulting in a 38% reduction in lower extremity injuries (RR = 0.62). This may be due to the fact that the hamstring eccentric training protocol of 21-30 weeks increased the eccentric strength of the hamstrings, improved the muscle balance between the hamstrings and quadriceps, and maximized the promotion of adaptive changes in hamstring strength and structure [23,[61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen RCT studies were included, all of which had a training frequency of 1-5 sessions per week, and a subgroup analysis showed that a hamstring eccentric training regimen lasting 21-30 weeks was the most effective in preventing lower extremity injuries, resulting in a 38% reduction in lower extremity injuries (RR = 0.62). This may be due to the fact that the hamstring eccentric training protocol of 21-30 weeks increased the eccentric strength of the hamstrings, improved the muscle balance between the hamstrings and quadriceps, and maximized the promotion of adaptive changes in hamstring strength and structure [23,[61][62][63].…”
Section: Discussionmentioning
confidence: 99%